AB0897 Functional disability and health-related quality of life in chinese patients with gout: a cross-sectional study. (15th June 2017) - Fu, T; Yin, R; Zhang, L; Zhang, Q; Xia, Y; Ji, J; Da, Z; Zhu, X; Li, L; Gu, Z
Abstract : Background: As the most common arthritis in adults, gout is a painful, inflammatory disease that may cause functional disability and decreased health-related quality of life (HRQoL). However, there are currently no known reported studies related to functional disability and HRQoL of gout patients from China. Objectives: This cross-sectional study aims to investigate the effect of demographic variables, disease parameters, and psychological status on functional disability and HRQoL of Chinese gout patients. Methods: A self-report survey was administered to 226 gout patients and 232 healthy individuals using the Short Form 36 health survey (SF-36) for HRQoL and the Health Assessment Questionnaire-Disability Index (HAQ-DI) for functional disability. Gout patients were asked to complete the 10 cm Visual Analog Scale (VAS) for total pain, the Patient Health Questionnaire (PHQ-9) for depression, and the Generalized Anxiety Disorder (GAD-7) questionnaire for anxiety. Blood samples were taken to examine the level of uric acid (UA). Independent samples t-tests, Chi square tests, spearman and/or pearson correlation and multiple linear regression were used to analyze the data. Results: Our results found that individuals with gout have poorer HRQoL compared to healthy controls and the mean disability score was 0.32 (SD 0.54), representing mild disability. SF-36 and almost all components of the SF-36 score were associated with place of residence, hypertension, DM, cardiovascular disease, disease duration, number of flares/last year, total pain, number of tophi, presence of tender joints, colchicines use, corticosteroids use, depression, and anxiety ( p <0.05). This variable was also significantly related to the HAQ-DI score ( p <0.05). Additionally, there were significant relationships among age, income/year, allopurinol use and HAQ-DI ( p <0.05). Stepwise multiple linear regression identified number of flares/last year, place of residence, depression and DM as predictors of functional disability. Disease status (total pain, number of flares/last year, presence of tender joints, cardiovascular disease, colchicine and corticosteroids use) and psychological disorders (depression and anxiety) were significantly accounted for poor HRQoL. Conclusions: Chinese gout patients experienced mild disability and poor HRQoL. Disease status and psychological status were important risk factors linked to functional disability and HRQoL in Chinese gout population. These data suggest medical personnel should pay more attention to functional disability and HRQoL of gout patients and make suitable interventions to relieve their psychological disorders and finally to reduce their functional ability and improve their HRQoL. Acknowledgements: This study was supported by Grants from the Chinese National Natural Science Foundation (no. 81671616 and 81471603). Disclosure of Interest: None declared